A case of coexistence of the FGFR3 and KIAA0753 gene mutation in thanatophoric dysplasia type 1 - Torres-Salinas, Carlos (2023)
Introduction: Thanatophoric dysplasia type 1 is a form of lethal skeletal dysplasia, it is characterized by disproportions of the axial-appendicular skeleton in addition to short stature, macrocephaly, frontal prominence, narrow thorax, femoral bowing and micromelia. Case report: 38-week-old male neonate, born by elective cesarean section due to skeletal malformations and polyhydramnios. The clinical evolution showed progressive deterioration over time and despite the different oxygenatory and ventilatory support devices. Conclusions: For its study, obstetric ultrasound, physical examination and radiographic findings are important. However, the diagnosis must be confirmed through a genetic study in order to discover new variants or associations, as well as to make known their real case mix in a certain region.